Sistem Informasi Pengolahan Kas Sekolah Pada MTs Ibnu Hajar Serasan - Jauhari, Dedy; Dwi Nurul Huda; Frisca Oktaria (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2018)
In each company , agencies , organization or business entity will give salary as compensation from work an employee , besides the provision of basic salary its employees , every agency often give a bonus besides basic salary to spur performance and productivity work employees because an employee who receive the bonus had to close some certain criteria concerning their discipline, performance, and productivity according to set by each agencies or company. For any effort who had computer-based information system in their business activities so need the support system the decision to determine employees will that has priority to get a bonus based on with the performance and their productivities are and can menentukkan the size of the bonus deserve to the workers.The support system this decision also could be useful to monitor employee performance from time to time .This system can also be used as a reference in the determination of the next step for employees who performed well or not .In this research will be appointed a case of making an application that can be applied in the determination of a employee with the weighted prodiuct made in one form website based information system. The research is conducted by a method of qualitative and collecting data which can help in building this application.Then also conducted a review the needs of users in the process of input and output.So that found a system that not only can do data storage and calculations, bonus but also can edit, erasing the. This application made by a programming language php and html with tools application Visual Studio Code, MySQL as databases and XAMPP as servers to run this.